Accuracy of Brain Multimodal Monitoring to Detect Cerebral Hypoperfusion After Traumatic Brain Injury*. Issue 2 (February 2015) - Bouzat, Pierre; Marques-Vidal, Pedro; Zerlauth, Jean-Baptiste; Sala, Nathalie; Suys, Tamarah; Schoettker, Patrick; Bloch, Jocelyne; Daniel, Roy T.; Levivier, Marc; Meuli, Reto; Oddo, Mauro
<x xml:space="preserve">Abstract</x> Objective: To examine the accuracy of brain multimodal monitoring—consisting of intracranial pressure, brain tissue PO2, and cerebral microdialysis—in detecting cerebral hypoperfusion in patients with severe traumatic brain injury. Design: Prospective single-center study. Patients: Patients with severe traumatic brain injury. Setting: Medico-surgical ICU, university hospital. Intervention: Intracranial pressure, brain tissue PO2, and cerebral microdialysis monitoring (right frontal lobe, apparently normal tissue) combined with cerebral blood flow measurements using perfusion CT. Measurements and Main Results: Cerebral blood flow was measured using perfusion CT in tissue area around intracranial monitoring (regional cerebral blood flow) and in bilateral supra-ventricular brain areas (global cerebral blood flow) and was matched to cerebral physiologic variables. The accuracy of intracranial monitoring to predict cerebral hypoperfusion (defined as an oligemic regional cerebral blood flow < 35 mL/100 g/min) was examined using area under the receiver-operating characteristic curves. Thirty perfusion CT scans (median, 27 hr [interquartile range, 20–45] after traumatic brain injury) were performed on 27 patients (age, 39 yr [24–54 yr]; Glasgow Coma Scale, 7 [6–8]; 24/27 [89%] with diffuse injury). Regional cerebral blood flow correlated significantly with global cerebral blood flow (Pearson r = 0.70, p < 0.01). Compared with normal regional cerebral blood flow (n = 16), low regional cerebral blood flow (n = 14) measurements had a higher proportion of samples with intracranial pressure more than 20 mm Hg (13% vs 30%), brain tissue PO2 less than 20 mm Hg (9% vs 20%), cerebral microdialysis glucose less than 1 mmol/L (22% vs 57%), and lactate/pyruvate ratio more than 40 (4% vs 14%; all p < 0.05). Compared with intracranial pressure monitoring alone (area under the receiver-operating characteristic curve, 0.74 [95% CI, 0.61–0.87]), monitoring intracranial pressure + brain tissue PO2 (area under the receiver-operating characteristic curve, 0.84 [0.74–0.93]) or intracranial pressure + brain tissue PO2+ cerebral microdialysis (area under the receiver-operating characteristic curve, 0.88 [0.79–0.96]) was significantly more accurate in predicting low regional cerebral blood flow (both p < 0.05). Conclusion: Brain multimodal monitoring—including intracranial pressure, brain tissue PO2, and cerebral microdialysis—is more accurate than intracranial pressure monitoring alone in detecting cerebral hypoperfusion at the bedside in patients with severe traumatic brain injury and predominantly diffuse injury.